On Peers and Copyright: Why the EU Should Consider Collective Management of P2P - Quintais, João Pedro (Munich Intellectual Property Law Center - MIPLC, 2012)
This book analyzes the EU's approach to P2P, a digital age technology that highlights the tensions between the Internet and a territorial and fragmented copyright law. It aims at providing the necessary legal qualification and context to understand why the EU, while following an economic and socially onerous path, has thus far failed to achieve its deterrence goals. It is argued that a solution to this conundrum must be based on the use of copyright law and policy as tools for market organization and innovation growth, with respect for rights holders and users (sometimes) opposing interests and the existing legal framework. The best answer to mass online P2P uses seems to be that of collective rights management, as it offers an organized licensing and remuneration system compatible with the interests of stakeholders. This is especially true in the EU, home to a developed and sophisticated market of CMOs, subject to numerous ECJ and Commission decisions, as well as varying EU institutional approaches, all pointing towards a preference for multi-territorial and pan-European licensing models. In this context, this book tests the compatibility of several non-voluntary and voluntary approaches to P2P with international treaties, the acquis or simply strategic policy considerations.